2008
DOI: 10.2217/17460794.3.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Cell Entry

Abstract: The initial steps of viral infection involve the specific attachment of the viral particle to receptor(s) on the cell surface, followed by internalization of the virus into the cell and the subsequent uncoating of the virion to release the transcriptionally active particle. These events are essential for the successful initiation of a virus replication cycle and play an important role in tissue tropism and pathogenesis of viruses. Rotaviruses, the leading cause of severe childhood diarrhea, principally infect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 97 publications
0
16
0
3
Order By: Relevance
“…The other three virus strains tested depend on clathrin-mediated endocytosis (caveolin-dependent or macropinocytosis uptake were ruled out). The findings in this work could help to clarify the different, sometimes even contradictory results which have been reported in the literature when characterizing different rotavirus strains (22). For instance, different results have been reported for the role of low pH on entry and for the role of the Ca 2ϩ concentration necessary for viral uncoating.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The other three virus strains tested depend on clathrin-mediated endocytosis (caveolin-dependent or macropinocytosis uptake were ruled out). The findings in this work could help to clarify the different, sometimes even contradictory results which have been reported in the literature when characterizing different rotavirus strains (22). For instance, different results have been reported for the role of low pH on entry and for the role of the Ca 2ϩ concentration necessary for viral uncoating.…”
mentioning
confidence: 61%
“…Using as a model MA104 cells and the simian rotavirus RRV, we have proposed that rotavirus cell entry is a complex multistep process that involves the two virus surface proteins and several cell receptors, including sialic acids, gangliosides, integrins ␣2␤1, ␣4␤1, ␣v␤3, and ␣x␤2, and the heat shock cognate protein hsc70 (22). We have also shown that depletion of cholesterol from the cellular membrane severely impairs the infectivity of rotavirus (19,50) and have suggested that sphingolipid-and cholesterol-enriched membrane lipid microdomains might be involved in rotavirus cell entry, since the virus and its receptors associate with these domains at early times during infection (23).…”
mentioning
confidence: 99%
“…Several proteins participate in the process that enables rotaviruses to enter cells (Isa et al, 2008). However, until now, research on rotavirus receptor proteins has only been carried out on MA104 and Caco-2 cell lines using rotaviruses adapted to them (Isa et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Integrin αvβ3 has been found in MA104 and Caco-2 cells (Guerrero et al, 2000a;Isa et al, 2008) and it has also been proposed as a rotavirus coreceptor, together with integrins α4β1, and αxβ2 (Coulson et al, 1997;Ciarlet et al, 2001;Graham et al, 2006). Th e Hsc70 and integrin αvβ3 are known to be located in the lipid raft microdomains of the cytoplasmic membrane (Isa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The initial step in rotaviral infection is virus attachment, performed after several reactions between the viral surface spike protein VP4 and the respective receptors on the cell membrane of host cells, such as integrins (Coulson et al, 1997) and heat shock protein Hsc70 (Isa et al, 2008). Some strains of the virus require the presence of sialic acid on the cell surface for efficient binding, but the great majority (of animal or human origin) is sialic acid-independent (Ciarlet and Estes, 1999).…”
Section: Transmission Of the Virus And Patho-genesis Of The Infectionmentioning
confidence: 99%